Redefining postpartum hemorrhage - Adhikari, S.; Bista, K.D.; Rana, A. (Journal of Institute of Medicine Nepal, 2007)
In the prospective study conducted in TUTH; 300 women with the active management of labour were enrolled; visual estimation of blood loss (volume criteria) was found to poorly correlate with changes in hemoglobin and hematocrit with unacceptably low sensitivity (3.4%) and specificity (93.4%) compared to the hemoglobin criteria (sensitivity 80.7%&specificity 93.9%) or the hematocrit criteria (sensitivity 89.7% & specificity 88.1%); thus suggesting redefinition of PPH in order to identify larger number of women with this problem; which may aid to bring down the morbidity and mortality associated with PPH. Journal of Institute of Medicine Vol.27(3) 2005